Agnara cavernicola, the second troglophilic terrestrial isopod species (Isopoda: Oniscidea) from Iran - Bakhshi, Yaser; Kashani, Ghasem M.; Sadeghi, Saber; Darvishnia, Hamid (Journal of natural history, 2021)
The first cave-dwelling terrestrial isopod species of the genus Agnara Budde-Lund, 1908 is described from Zarneh Cave, western Iran. Agnara cavernicola Bakhshi and Kashani, sp. nov. is characterised by a reduced number of ommatidia and body pigments. Moreover, it differs from the congeneric species by the shape of male pleopod exopodites I and male pereopods VII. http://urn:lsid:zoobank.org:pub:B0DDD1CE-B6B6-44A9-A8AC-E2AF3F0EBE54